2009
DOI: 10.1086/596629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Heteroresistant Vancomycin-IntermediateStaphylococcus aureusBacteremia versus Those of Methicillin-ResistantS. aureusBacteremia

Abstract: hVISA bacteremia was significantly associated with prolonged bacteremia duration, greater rates of complications, and emergence of rifampin resistance, compared with MRSA bacteremia. However, no significant difference in mortality existed between patients with hVISA bacteremia and those with MRSA bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 21 publications
3
101
3
Order By: Relevance
“…Those authors were not able to relate these complications to low serum vancomycin levels. The infection-attributable mortality for hVISA was similar to that for MRSA bacteremia (193).…”
Section: Clinical Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Those authors were not able to relate these complications to low serum vancomycin levels. The infection-attributable mortality for hVISA was similar to that for MRSA bacteremia (193).…”
Section: Clinical Studiesmentioning
confidence: 62%
“…Essentially, an hVISA isolate is an S. d S. aureus with reduced susceptibility (SA-RVS) is defined as follows: (i) MIC of Ն4 g per ml (91,306) or (ii) area under vancomycin concentrationkill curve of Ն0.9 of the AUC of type strain Mu3 (124). hVISA is defined as follows: (i) VSSA strain that upon subculture stably produces subcolonies with MICs in the VISA/VRSA range at a frequency of Ն1 ϫ 10 6 according to the population analysis profile (PAP) (114); (ii) AUC ratio of Ն0.9 of the AUC of type strain Mu3, referred to as PAP/AUC (48,118,155); or (iii) modified high-inoculum Etest read at 48 h (193,194).…”
Section: Heterogeneous Vancomycin-intermediate Staphylococcus Aureus mentioning
confidence: 99%
“…Vancomycin MICs of Ͼ1 g/ml have been associated with hVISA (2,12,33), but this is not a strong indicator for hVISA because Etest and Sensititre reported equally high MICs in the vancomycin-susceptible isolates. The incidence of hVISA in other hospitals has varied, ranging from 0 to 50% (3,4,7,13,21,22,23,25,28,29,34,35,50,52,54). The type of screening test used to detect hVISA and the number of isolates screened are responsible for this wide range.…”
Section: Figmentioning
confidence: 99%
“…Patients who have serious high-inoculum infections (i.e., infective endocarditis, medical device infections, etc.) with MRSA and for which the strain has been identified as heteroresistant vancomycin-intermediate S. aureus (hVISA) are also more likely to experience prolonged days of bacteremia, increased complications, multiple drug resistance, and relapse or recurrence of infection than those patients with susceptible strains (12)(13)(14)(15)(16)(17)(18). It has been demonstrated that some percentage of hVISA infections exist within the vancomycin susceptibility range and that the prevalence of these strains increases as the MIC reaches up to the breakpoint of 2 mg/liter (19)(20)(21).…”
mentioning
confidence: 99%